PRINSIP SEKRETARIAT PANITIA PEMILIHAN KECAMATAN PADA PEMILIHAN BUPATI AGAM TAHUN 2015 - Aprinal, Fery; Ariany, Ria; Tamrin, Tamrin (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
This Research of district election committee secretariat as work principle in the regent and vice-regent election of Agam 2015. District Election Committee (DEC) Secretariat for the Agam Regent and Vice-Regent Election 2015 was appointed by the current Agam Regent. The regent who appointed the DEC Secretariat for the election of Agam Regent and Vice-Regent 2015 nominated himself to be the Agam Regent for the 2016-2021 period. This research uses the qualitative descriptive method and is intended to describe and analyze the principles of the electoral management bodies which apply to the DEC Secretariat in carrying out the Agam Regent and Vice-Regent Election 2015. This research uses 7 (seven) core principles of electoral management bodies, which are independent, impartial, integrity, transparent, efficient, professional, and willingness to serve. The result of this research shows that (1) District Election Committee (DEC) Secretariat for the election of Agam Regent and Vice-Regent 2015 could not fully exercise the principles of organizing election and (2) there are 3 factors that influence the DEC Secretariat in carrying out the Agam Regent and Vice-Regent Election 2015, which are regulation, communication, and competence. The appointment of district election committee secretariat by regent or mayor can affect of district election committee secretariat in carrying out the principle.